Information and communicatiaon technology : International Conference, ICT-EurAsia 2013, Yogyakarta, Indonesia, March 25-29, 2013. Proceedings - Neuhold, Erich J.; Tjoa, A Min; Weippl, Edgar; You, Ilsun; Mustofa, Khabib (Lecture notes in computer science, 2013)
This book constitutes the refereed proceedings of the International Conference on Information and Communication Technology, ICT-EurAsia 2013, and the collocation of AsiaARES 2013 as a special track on Availability, Reliability, and Security, held in Yogyakarta, Indonesia, in March 2013. The 62 revised full papers presented were carefully reviewed and selected from a numerous submissions. The papers are organized in topical sections on e-society, software engineering, security and privacy, cloud and internet computing, knowledge management, dependable systems and applications, cryptography, privacy and trust management, network analysis and security, and multimedia security.